1996
DOI: 10.1042/bj3190783
|View full text |Cite
|
Sign up to set email alerts
|

Multiple factors regulating the expression of human thromboxane synthase gene

Abstract: Characterization of the 5.5 kb promoter of human thromboxane synthase (TS) gene revealed a proximal positive regulatory sequence (PPRS, -90 to -25 bp) and several distal repressive elements. The maximal promoter activity was found to reside within the first 285 bp, approximately 75% of which was contributed by the PPRS. The sequence between -365 and -665 bp exerted a strong repressive effect (approximately 55%) on reporter gene expression independent of orientation and position, consistent with properties expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…This finding is in agreement with the fact that multiple initiation sites are often observed in genes utilizing a TATA-less promoter (24,25). Like the human H-PGDS gene, the human cyclooxygenase-1 and thromboxane synthase genes involved in prostanoid biosynthesis also have TATA-less promoters with multiple transcription initiation sites (26,27).…”
Section: Discussionsupporting
confidence: 76%
“…This finding is in agreement with the fact that multiple initiation sites are often observed in genes utilizing a TATA-less promoter (24,25). Like the human H-PGDS gene, the human cyclooxygenase-1 and thromboxane synthase genes involved in prostanoid biosynthesis also have TATA-less promoters with multiple transcription initiation sites (26,27).…”
Section: Discussionsupporting
confidence: 76%
“…A point mutation at the NF-E2 binding site (TGATTCA to GGATCCA) in pMCϪ280/ϩ137, called pMCϪ280/ϩ137-mNF-E2, was generated by PCR. NF-E2 cDNA was obtained by reverse transcription-PCR from total MEG-01 cellular RNA (17) and first subcloned into TA vector and then into the pcDNA3.1 eukaryotic expression vector (Invitrogen) at the BamHI/HindIII site. All constructs generated by PCR were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Role of NF-E2 Site in TXAS Gene Transcription in a Native Chromatin Context-In transient transfection experiments, the Ϫ300/Ϫ40 TXAS upstream promoter sequence, particularly at the NF-E2 site between Ϫ83 and Ϫ77, is crucial for transcriptional activity in several types of cells (15,17,18,20). To test whether NF-E2 activates the TXAS gene in a natural chromatin context, we generated a mutation at the NF-E2 site in the pMCϪ280/ϩ137 minichromosome (pMCϪ280/ϩ137-mNF-E2) and stably transfected it into HEL cells.…”
Section: Mnase-coupled Southern Blot Analyses Of Txas Promoter/ Reportermentioning
confidence: 99%
See 1 more Smart Citation
“…We also have observed that TXS mRNA is induced in an inflammatory model of hydronephrosis characterized by infiltration of macrophages in the renal interstitium (8). Although the transcriptional regulatory regions of the human (9) and mouse TXS (10) genes have been cloned, analysis of their gene transcription has not yet been extensively performed, and any role of the peroxisome proliferatoractivated receptor (PPAR) in TXS gene transcription has never been examined.…”
mentioning
confidence: 99%